HUBUNGAN LITERASI LINGKUNGAN DAN LITERASI MATEMATIS TERHADAP KEMAMPUAN COMPUTER SELF EFFICACY - M. Syaif Amrullah Alqusyairi; Suherman Suherman; Farida Farida (LPPM Universitas Bina Bangsa, 2021)
The purpose of this study is to determine the relationship between environmental literacy and mathematical literacy on the ability of students' Computer Self Efficacy. This quantitative study uses a Correlational Design research design. The data collection techniques in this study were environmental literacy tests, mathematical literacy tests, and a Computer Self Efficacy ability questionnaire. The data analysis technique used is Simple and Multiple Linear Regression. Based on the results obtained from research and calculations of Simple and Multiple Linear Regression analysis, it was concluded that there is a relationship between environmental literacy and the ability of Computer Self Efficacy of students, there is a relationship between mathematical literacy and the ability of Computer Self Efficacy of students, and there is a relationship between environmental literacy and mathematical literacy with the ability of students' Computer Self Efficacy. The magnitude of the influence of environmental literacy and mathematical literacy on the ability of Computer Self Efficacy is 39.2%.